Farinha de minhoca e glúten de trigo 90 na alimentação de carpa comum - Ferreira, Iara Evelim da Silva (2022)
The common carp, Cyprinus carpio, is a fish of great demand in the market, in addition to the ease of its production, but the nutritional studies of the species still have gaps for further research. Thus, the objective was to evaluate the applicability of different levels of inclusion of earthworm meal and gluten meal replacing fish meal in the formulation of practical diets for common carp (Cyprinus carpio). The experiments were carried out at the Instituto Federal do Espírito Santo from December 2021 to February 2022, in a completely randomized design (DIC), where the treatments corresponded to levels of 0, 25, 50, 75 and 100% of the crude protein derived from of earthworm flour (experiment 1) and 0, 25, 50, 75 and 100% of crude protein derived from gluten flour. The experimental units consisted of twelve juveniles of colored carp in boxes with a useful volume of 40L in a water recirculation system, equipped with biological filtration. Productive performance was evaluated by weight gain (GP), protein efficiency rate (TEP) and specific growth rate (TCE). Based on the results obtained in the present study, it can be concluded that levels of up to one hundred percent replacement of fish meal by worm or wheat meal can be used in the feeding of juvenile common carp without harming the zootechnical development of the animals. animals.